Determinants of Economic Growth in Bali Province - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Dyah Purwanti; Sigit Budiantono; I Dewa Gede Sunanjaya (Institute of Accounting Research and Novation (IARN), 2023)
Economic growth is one of the goals of economic development. Sustainable economic growth has an impact on various other economic and social sectors. This research aims to see the effect of investment, regional income and human development index (HDI) on economic growth in Bali Province. Data from the BPS-Statistics Bali for 20 11-2021. The statistical method used multiple linear regression with panel data. Based on panel model testing, the fixed model is the best. Simultaneously, all variables affect the rate of economic growth. Partially, investment, regional income and human development index have a significant positive effect on the economic growth rate in Bali. Based on the results of this study, comprehensive policies related to macro-social economics are needed so that the level of economic growth continues to increase sustainably.